Candida spp. Determination and Th1/Th2 Mixed Cytokine Profile in Oral Samples From HIV+ Patients With Chronic Periodontitis - Lomeli-Martinez, Sarah M.; Valentin-Goméz, Eulogio; Varela-Hernández, Juan J.; Alvarez-Zavala, Monserrat; Sanchez-Reyes, Karina; Ramos-Solano, Moises; Cabrera-Silva, Rodolfo I.; Ramirez-Anguiano, Victor M.; Lomeli-Martinez, Manuel A.; Martinez-Salazar, Silvia Y.; González-Hernández, Luz A.; Andrade-Villanueva, Jaime F. (Frontiers in Immunology, 2019)
Background: Chronic periodontitis (CP), caused by bacteria and fungi, appears in up to 66% of HIV-patients. The impact and association of HIV-treatment (HAART) and Candida itself has not been properly evaluated in the development and progression of CP. The immunopathogenesis is characterized by CD4+ T-cells activation and the balance between the T-helper 1 (Th1) and T-helper 2 (Th2) or a mixed cytokine profile. Currently, the associated causes of an immune response in HIV-patients with CP is controversial. Our aims were the determination of Candida spp. and cytokine profile in oral samples from HIV-positive patients with CP, considering the CD4+ T cells levels and HAART use. Methods: From 500 HIV-positive patients evaluated, 228 patients were enrolled. Patients were separated in groups: (A) n = 53 (≤200 CD4+ T-cells on HAART); (B) n = 57 (≤200 CD4+ T-cells without HAART); (C) n = 50 (>200 CD4+ T-cells without HAART); (D) n = 68 (>200 CD4+ T-cells on HAART). Candida spp. were isolated from the oral biofilm and crevicular fluid in CHROMagar and confirmed by endpoint PCR. Cytokine levels were measured by beads-based immunoassay in saliva by flow cytometry. Results: 147 patients (64.5%) were positive to Candida spp. and 204 strains were isolated; 138 (67.6%) were C. albicans and the remaining C. non-albicans species (C. glabrata>C. tropicalis>C. krusei>C. dubliniensis). In this study, CHROMagar showed good sensitivity (95%) but poor specificity (68%); since of the 152 samples identified as C. albicans, only 131 were confirmed by PCR; from the 10 samples identified as C. glabrata, only six were confirmed. Finally, of the 42 samples detected as C. tropicalis, only five were confirmed. When evaluating Candida spp. presence, group A and D had higher isolation, while group B had the highest species diversity. Whereas, group C had a significant reduction of Candida spp. Despite the presence of Candida and HAART, we found a Th1/Th2 hybrid profile in the saliva of patients with low CD4+ T-cell count (group A). Conclusion: Abundance and diversity of the Candida spp. detected in HIV-patients with CP could be related to HAART and low CD4+ T-cells levels. Also, the immunosuppression might promote a local Th1/Th2 hybrid cytokine profile.